Four decades of chemistry in the UNESP/Araraquara. - Massabni, A. C.; Ernandes, JR; Melios, C. B. (Soc Brasileira Quimica, 2003)
FOUR DECADES OF CHEMISTRY IN THE UNESP/ARARAQUARA. This article describes the history of four decades of activities in the Institute of Chemistry of Araraquara, UNESP: the beginning, the evolution of undergraduate and graduate courses and the infra-structure of teaching and research.
Keywords: chemistry; UNESP; Araraquara